Higher ambient synaptic glutamate at inhibitory versus excitatory neurons differentially impacts NMDA receptor activity - Lulu Yao (Nature Portfolio, 2018)
Inhibitory interneurons play important roles in brain circuits and in several neuropsychiatric disorders. Here, the authors show that excitatory synapses onto interneurons vs. excitatory neurons differ in their ambient synaptic glutamate level, a finding with important implications for selective pharmacological targeting of inhibitory neuron NMDA receptors.